1986
DOI: 10.1007/bf02438961
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation delay by stable cAMP analogues in the slime moldPhysarum polycephalum

Abstract: Plasmodial cells of the slime moldPhysarum polycephalum become competent for sporulation following a prolonged period of starvation in darkness. Then sporulation can be induced by illumination. Microinjections of the stable (Sp)- and (Rp)-diastereoisomers of adenosine cyclic 3',5' monothionophosphate before and during a sensitive period from the start of illumination until 5 h after lead to a significant delay in the sporulation process.Both of the diastereoisomers of cyclic AMP prolong the time for sporangia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that the intracellular cAMP concentration of the Physarum polycephalum plasmodium spikes when development is induced by light (Akitaya, Ueda & Kobatake, ), and it continues to oscillate throughout development, including spiking again when fruiting body formation begins (Akitaya et al , ). These cAMP spikes in Physarum seem to be directly related to the enactment of development, as inhibitory cAMP analogues prevent fruiting (Brandt, Jastorff & Hildebrandt, ). As presented in Table , a homolog of the Dictyostelium discoideum acaA gene is upregulated in Physarum , while the acrA homolog is not, and a acgA homolog is absent.…”
Section: The Multicellular Sporocarpy Hypothesismentioning
confidence: 99%
“…Previous studies have demonstrated that the intracellular cAMP concentration of the Physarum polycephalum plasmodium spikes when development is induced by light (Akitaya, Ueda & Kobatake, ), and it continues to oscillate throughout development, including spiking again when fruiting body formation begins (Akitaya et al , ). These cAMP spikes in Physarum seem to be directly related to the enactment of development, as inhibitory cAMP analogues prevent fruiting (Brandt, Jastorff & Hildebrandt, ). As presented in Table , a homolog of the Dictyostelium discoideum acaA gene is upregulated in Physarum , while the acrA homolog is not, and a acgA homolog is absent.…”
Section: The Multicellular Sporocarpy Hypothesismentioning
confidence: 99%